Donbas geoelectrical structure - І.І. Рокитянський; А.В. Терешин (Геофизический журнал, 2022)
The Donbas was formed as the result of Late Devonian rifting of the East European craton. During the Carboniferous, the subsidence of the basin and sedimentation were at their maximum, and a 15-kilometer stratum of Carboniferous deposits formed in the Donbas. The total thickness of the deposits reaches more than 20 km. The next important event was folding, which occurred in the Late Triassic — Early Jurassic and Late Cretaceous — Early Tertiary. The inversion lifted the upper part of the folded Donbas and subsequent erosion exposed the Carboniferous coal-bearing strata on the surface of the earth. Deep electrical conductivity was studied by the methods of magnetovariational profiling (MVP) and magnetotelluric sounding (MTS). The first large survey (13 long-period MTS sites and 32 MTS points) was carried out in 1986; in 1988 another 30 MTS were performed. In 2012-2013, a profile of 15 MVP-MTS sites was made with modern instruments that allow obtaining more accurate results. The data interpretation yields the following conclusions. The intense Donbass electrical conductivity anomaly (DAE) runs along the main anticline of the folded Donbass. In the northwest, it continues in the DDD, in the southeast — on the Karpinsky swell. DAE parameters obtained by the MVP method: Based on the frequency response of the anomalous field, the total longitudinal conductance G = (8±2)×108S×m was estimated. Profile graphs of the anomalous field of geomagnetic variations give an estimate of the maximum possible depth of the anomalous currents center hmax.c.curr, which depends on the variations period. For DAE at the maximum frequency response Т0≈3600 s, it turns out to be equal to hmax.c.curr=18±2 km. The upper edge of the anomaly is estimated from MTS data. Most of the available 70 MTS ρк curves begin at periods of 0.1—1 s from approximately the same level of 15 Ohm·m±half an order of magnitude. This means that in the Donbass, the rocks of the upper approximately half-kilometer layer have, as a rule, electrical resistivity in the range of 5—50 Ohm·m. Deeper, the resistivity can increase to hundreds and thousands of Ohm·m or decrease to units or fractions of Ohm·m. An analysis of the MTS by area showed that objects of low resistance (LRO) are located in two conductive bands, the upper edge of which varies from 0.3 to 5 km. The bands are parallel to the DAE axis and can be considered as some part of the anomaly. A very large value of G leads to the assumption that the anomalous body extends to a considerable depth. When compared with the data of other geophysical methods, it turned out that the DAE spatially coincides with an intense (up to 90 mW/m2) linear anomaly of the deep heat flow. This fact suggests that the nature of the DAE lower part can be a partial melting of fluid-enriched heated local rocks or intrusion of mantle magma. The obtained geoelectric results support the idea of the modern tectonic activation in Donbas.